Changes in Clinical Characteristics of Community-Acquired Acute Pyelonephritis and Antimicrobial Resistance of Uropathogenic Escherichia coli in South Korea in the Past Decade - Ki Tae Kwon; Bongyoung Kim; Seong-yeol Ryu; Seong-Heon Wie; Jieun Kim; Hyun-uk Jo; Se Yoon Park; Kyung-Wook Hong; Hye In Kim; Hyun ah Kim; Mi-Hee Kim; Mi Hyun Bae; et al. (MDPI AG, 2020)
This study examined changes in the clinical characteristics of community-acquired acute pyelonephritis (CA-APN) in South Korea between the period 2010-2011 and 2017-2018. We recruited all CA-APN patients aged ≥19 years who visited eight hospitals in South Korea from September 2017 to August 2018, prospectively. Data collected were compared with those from the previous study in 2010-2012, with the same design and participation from 11 hospitals. A total of 617 patients were enrolled and compared to 818 patients' data collected in 2010-2011. Escherichia coli was the most common causative pathogen of CA-APN in both periods (87.3% vs. 86.5%, p = 0.680). E. coli isolates showed significantly higher antimicrobial resistance against fluoroquinolone (32.0% vs. 21.6%, p < 0.001), cefotaxime (33.6% vs. 8.3%, p < 0.001), and trimethoprim/sulfamethoxazole (37.5% vs. 29.2%, p = 0.013) in 2017-2018 than in 2010-2011. Total duration of antibiotic treatment increased from 16.55 ± 9.68 days in 2010-2011 to 19.12 ± 9.90 days in 2017-2018 (p < 0.001); the duration of carbapenem usage increased from 0.59 ± 2.87 days in 2010-2011 to 1.79 ± 4.89 days in 2010-2011 (p < 0.001). The median hospitalization was higher for patients in 2017-2018 than in 2010-2011 (9 vs. 7 days, p < 0.001). In conclusion, antimicrobial resistance of E. coli to almost all antibiotic classes, especially third generation cephalosporin, increased significantly in CA-APN in South Korea. Consequently, total duration of antibiotic treatment, including carbapenem usage, increased.